Measurement of the Maturity Level of Knowledge Management Implementation in Non-Ministry Government Institutions - Ambhita Sukma, Yan Andriariza; Sari, Risna (Jurnal Pekommas, 2021)
The government needs knowledge management to improve efficiency and effectiveness in the decision-making process. Knowledge management is one of the supporters in Bureaucratic Reform, which aims to encourage the realization of an effective and efficient organization, to make it happen, government agencies must be prepared to utilize the wealth of knowledge they have, by looking at knowledge management maturity level in government. Based on the research results, the maturity level for all LPNK is 133, which is at level 3 or Introduction, with knowledge management strategies: Formalizing knowledge management through regulations; Establish systems for identifying, creating, storing, sharing, applying and inventorying knowledge; Develop a system of providing incentives for employees; Develop measurement methods and indicators to assess the impact of knowledge contributions and initiatives; Form a cross-functional team to assist each work unit in solving problems encountered; Creating a recovery system to ensure operational activities continue despite critical situations, and Creating a systematic induction process for new employees.